HUBUNGAN MASA KERJA DAN SIKAP TENAGA KESEHATAN DENGAN PENGETAHUAN MENGENAI TRIAGE DI RUMAH SAKIT BHAYANGKARA BANDA ACEH - Anwar, Chairanisa; Mahmudin, Mahmudin; Asyura, Finaul; Widyasari, Ruri (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2024)
Triage memiliki fungsi penting di IGD terutama apabila banyak pasien datang pada saat yang bersamaan. Hal ini bertujuan untuk memastikan agar pasien ditangani berdasarkan urutan kegawatannya untuk keperluan intervensi. Studi pendahuluan terhadap 10 petugas kesehatan, rata-rata lama masa kerja berkisar antara 1-2 tahun. Tujuan Penelitian: Mengetahui hubungan sikap dan masa kerja dengan pengetahuan triage di Rumah Sakit Bhayangkara Banda Aceh tahun 2022. Metode Penelitian: Penelitian analitik dengan desain cross sectional, total sampel 66 orang tenaga kesehatan di Rumah Sakit Bhayangkara Banda Aceh. Teknik pengambilan sampel adalah stratified random sampling. Menggunakan uji chi-square dan analisa secara univariat dan bivariat. Hasil Penelitian : tidak ada hubungan P value 0,619 masa kerja, tidak ada hubungan P value 1,179 sikap tenaga kesehatan dengan pengetahuan tentang triage di Rumah Sakit Bhayangkara Banda Aceh tahun 2022. Saran: pengetahuan bagi tenaga kesehatan untuk menambah wawasan serta keterampilan terutama dalam keterampilan dalam kemampuan triage di instalasi gawat darurat.Kata Kunci: Masa Kerja, Sikap, TriageTriage has an important function in the ED, especially when many patients come at the same time. This aims to ensure that patients are treated in order of urgency for intervention purposes. Preliminary study of 10 health workers, the average length of service t ranges from 1-2 years. Research Objectives: To determine the relationship between attitude and tenure with triage knowledge at Bhayangkara Hospital Banda Aceh in 2022. Research Methods: An analytic study with a cross sectional design, a total sample of 66 health workers at Bhayangkara Hospital Banda Aceh. The sampling technique is stratified random sampling. Data collection distributed questionnaires through google forms. Using chi-square test and univariate and bivariate analysis. Research results: there is no relationship P value 0.619 years of service, there is no relationship P value 1.179 attitude of health workers with knowledge about triage at Bhayangkara Hospital Banda Aceh in 2022. Conclusion: There is no relationship between tenure and attitude of health workers with knowledge of triage at Bhayangkara Hospital Banda Aceh in 2022. Suggestion: knowledge for health workers to add insight and skills, especially in skills in triage abilities in emergency units.Keywords: tenure, attitude, triage